Electrochemically active water repelling perfluorinated polyaniline films - Dallas, P; Tomšík, E; Sang Jones, R; Xiao, A; Milnes-Smith, E; Grobert, N; Porfyrakis, K (Elsevier, 2019)
Water repelling, perfluorinated, polyanilines and their composites with multi-wall carbon nanotubes are synthesized using interfacial polymerization in either flake-like or fibrillar shapes. This class of polyanilines exhibits electrochemical activity, capacitive behaviour, and a contact angle of 119–125° with water. The addition of multi-wall carbon nanotubes facilitates the control of the polymer morphology and increases the specific capacitance of the material. We obtained microfibers or flake-like morphologies depending on the amount of multi-wall carbon nanotubes added in the organic phase and through cyclic voltammetry, impedance spectroscopy and galvanostatic charge-discharge, we evaluated the effect of the backbone geometry and the addition of nanotubes on the electrochemical properties of the composites and the pristine polymers. The capacitance of the linear 3-perfluoroctyl polyaniline is consistently better than the cross-linked 4-perfluoroctyl polyaniline, where the para position relative to the amine group is blocked by fluorocarbon chains.